PENGARUH PENGETAHUAN MENDETEKSI KEKELIRUAN DAN ETIKA PROFESI TERHADAP KUALITAS AUDIT DENGAN PERTIMBANGAN TINGKAT MATERIALITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Kantor Akuntan Publik se Sumatera) - Adrian Freddy Hilman; Muhammad Rasuli; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study is aimed at analyzing the effect of knowledge to detect errors and professional ethics toward consideration of materiality level as well as audit quality, to analyze consideration of materiality level as variable which mediate the effect of knowledge to detect errors and professionalal ethics toward the quality of audit. The study was conducted in Public Accountant Office in Sumatera. There are 108 questioner that have been given to the Public Accountant Office in Sumatera trough questionnaires. The data collecting method used is questionnaire which is sent by mail (mail survey) which is called primary data. Data quality is tested by validity and reliability test. Classic assumption tests used are normality, hetericedasticity, multicolinierity, and autocorrelation. Hypotesis test is done by path line and T-test. The Methods of data analysis in this study is use multiple linear regression with SPSS version 17.0. Validity and reliability test result show that knowledge to detect errors, professional ethics, consideration of materiality level and quality of audit are declare valid. Classic assumption test show all data regression used gas been passed from normality test, heterocedasticity, multicolinierity test and autocorrelation test. The result of path line analysis indicates that the knowledge to detect errors and professional ethics does not directly affect the quality of audit, but is mediated by the consideration of materiality level.Keywords: Knowledge, Ethics, Materiality, and Quality